2019
DOI: 10.1186/s13638-019-1412-6
|View full text |Cite
|
Sign up to set email alerts
|

Realistic propagation effects on wireless sensor networks for landslide management

Abstract: This paper presents the development of propagation models for wireless sensor networks for landslide management systems. Measurements of path loss in potential areas of landslide occurrence in Thailand were set up. The effect of the vegetation and mountain terrain in the particular area was therefore taken into account regarding the measured path loss. The measurement was carried out with short-range transmission/reception at 2400 MHz corresponding to IEEE 802.15.4 wireless sensor networks. The measurement set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…When you must check the actual system performance in a series of ways using different parameters and are cost-effective and hardworking the process of simulation will be followed. Simulations are the replications of realism for exploring the model, it offers to arrange and format the algorithm properties (Shutimarrungson & Wuttidittachotti, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When you must check the actual system performance in a series of ways using different parameters and are cost-effective and hardworking the process of simulation will be followed. Simulations are the replications of realism for exploring the model, it offers to arrange and format the algorithm properties (Shutimarrungson & Wuttidittachotti, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…According to researchers in (Shutimarrungson & Wuttidittachotti, 2019) investigated the result of two non-fading models of propagation named free space and two ray ground model, by the key features and outcomes of the ad-hoc routing schemes like DSR, AODV and Location-Aware Routing scheme in terms of average throughput, delay, and routing overhead. The authors observed that the act and efficiency of the LAR1 routing protocol is top, and the performance of DSR protocol is worst as radio verity increase.…”
Section: Related Literaturementioning
confidence: 99%
“…30 Experimental studies have shown that in areas with multipath loss, path loss includes log-normal distribution and shadowing effects. 9…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…These are generally animal behavior monitoring, industrial detection, health monitoring, consumption, and military applications. [1][2][3][4][5][6][7][8][9][10][11] Besides these applications, this technology is also commonly used for precision agriculture applications in the various vegetation environments such as fruit orchard. [5][6][7] The usage of wireless sensor networks (WSN) has become significant with the aim of monitoring and management, especially in vegetative environments.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies measure the size of foliage depth and create a model with location-based image processing [22]. In MED models such as Weissberger, ITU Recommendation (ITU-R), LITU-R, FITU-R, and COST235 [23][24][25][26][27][28][29], the path loss changes as an exponential function of frequency and distance. It should be noted that these five models are made in areas with foliage depths <1 km.…”
Section: Fundamentals Of Foliage Path Loss Modelsmentioning
confidence: 99%